Assessment of the effectiveness of laser-acoustic transformation - Rybalka, A. I.; Megel, Y. E.; Kalimanova, I. (Technical University of Sofia, 2019)
For some biotechnological technologies, there is a problem of separating living cells or destroying their membranes in order to obtain individual elements of the inner structure of the cell. This is usually done using microsurgical operations. In practice, the method of obtaining individual cell fragments without surgery using an acoustic wave is of interest. In this paper, a mathematical model and the results of modeling the process of the formation of an acoustic pressure wave in a liquid biological solution for the destruction of the membrane of a biological object is considered.
Keywords: biotechnologies; laser; optoacoustic; membrane